MOTHER'S SATISFACTION WITH BASIC IMMUNIZATION SERVICES DURING THE COVID 19 PANDEMIC: MIXED METHOD - Allania Hanung; Atik Mahmudah; Raudatul Munawarah; Devi Suharani (Proceeding of International Conference on Science, Health, And Technology, 2022)
Background of this research is decrease immunization efficient in pandemic covid-19. Based on routine immunization data reports for October 2021, complete basic immunization coverage has only reached 58.4% of the target 79.1%. The purpose of this study was to determine the satisfaction of mothers under five with immunization services during the Covid-19 pandemic at the Banyudono I Health Center. Objective This research is a research mix ed methods. With research techniques using nonprobability sampling, accidental sampling, and for samples with a qualitative approach, using saturated samples. The research was conducted on February 22 and March 1, 2022. Methods from the results of data analysis, it can be seen that from 4 3 respondents mothers who have toddlers 0-24 months with a frequency of 28 respondents said they were not satisfied (65.5%), 15 respondents said they were satisfied (34.9%), and based on the results of interviews from 3 Respondents one mother said they were satisfied and 2 mothers said they were not satisfied with the immunization service. Results for health workers, especially midwives and the registration section at the Banyudono I Health Center, is to improve the registration system so that it can improve better services, and create patient comfort when visiting the Banyudono I Health Center